On paramagnetic phases of the Potts model on a Bethe lattice in the presence of competing interactions - Ganikhodjaev, Nasir; Rahmatullaev, Anasbek (Institute of Physics Publishing, 2013)
We consider a Potts model on a Bethe lattice with competing nearest-neighbour J and next-nearest-neighbour interactions Jp. The phase diagram of this model was studied by Ganikhodjaev et al. In this paper we investigate the problem of phase transition for the considered model and show that for some parameter values of the model there is phase transition.